Association of aberrant right subclavian artery with abnormal karyotype and microarray results. (12th July 2017) - Svirsky, Ran; Reches, Adi; Brabbing‐Goldstein, Dana; Bar‐Shira, Anat; Yaron, Yuval
Abstract: Objectives: The objective of this study is to evaluate the incidence of chromosomal aberration (both microscopic and sub‐microscopic) in fetuses with an aberrant right subclavian artery (ARSA) detected by ultrasonographic anomaly scan. Methods: The study included 62 pregnant women whose fetuses were diagnosed with ARSA who were referred for genetic counseling. Of these, 55 patients underwent amniocentesis and 7 declined invasive testing. All 55 amniocentesis samples were tested by standard G‐banding and chromosomal microarray, except for 2 samples for which only karyotype and fluorescence in situ hybridization for 22q11.2 deletions were performed. Results: Of the 55 women who underwent amniocentesis, 5 were detected with trisomy 21 (9.1%), all of whom had additional ultrasound findings. Among the 14 fetuses with ARSA and additional ultrasound findings, the incidence of trisomy 21 was 35.7%. In fetuses with isolated ARSA, no chromosomal aberrations were detected by standard cytogenetic analysis and only one (1.9%) deleterious copy number variants (CNV) was detected by chromosomal microarray. Conclusion: Aberrant right subclavian artery with additional ultrasound findings constitute a strong predictor for aneuploidy. However, when ARSA is found in isolation, it confers no increased risk for aneuploidy or pathogenic CNVs. © 2017 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? A successful demonstration of the right subclavian artery is feasible by ultrasonography in fetuses in the first and second trimester. There is a high prevalence of trisomy in fetuses with aberrant right subclavian artery and additional ultrasound findings. What does this study add? When aberrant right subclavian artery is found in isolation, it confers no increased risk for aneuploidy. When aberrant right subclavian artery is found in isolation, it confers no increased risk for pathogenic copy number variants